(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
This study seeks to find out what opportunities the Music Department at “Juhász Gyula” Faculty of Education of the University of Szeged (SZTE JGYPK) has had, in the course of its history, to familiarize with rarely heard pieces of music, and to hold lectures on the history of music, which, by their specific subject matter, served to expand knowledge and did not belong to the official curriculum. A longitudinally arranged research summarizes the special presentations and concerts of Hungarian and foreign lecturers visiting the department. Out of the works of Hungarian composers, we cover the works and impact of György Ránki, Zsolt Durkó and Máté Hollós.